Chemical abundances of Seyfert 2 AGNs, I: comparing oxygen abundances from distinct methods using SDSS - Dors, Oli L. (2020)
We compare the oxygen abundance (O/H) of the narrow-line regions (NLRs) of Seyfert 2 AGNs obtained through strong-line methods and from direct measurements of the electron temperature (Te-method). The aim of this study is to explore the effects of the use of distinct methods on the range of metallicity and on the mass-metallicity relation of active galactic nuclei (AGNs) at low redshifts (z<~0.4). We used the Sloan Digital Sky Survey (SDSS) and NASA/IPACExtragalactic Database (NED) to selected optical (3000